(x + y)3 = x3 + 3.x2.y +
3.x.y2 + y3
Exemplos:
1- (5a + 7b)3 = (5a)3 + 3.(5a)2.7b
+ 3.5a.(7b)2 + (7b)3 = 125a3 + 525a2b
+ 735ab2 + 343b3
2- (6g + 3m)3
= (6g)3 + 3.(6g)2.3m + 3.6g.(3m)2 + (3m)3
= 216g3 + 324g2m + 162gm2 + 27m3
3- (8h + 2n)3 = (8h)3 + 3.(8h)2.2n
+ 3.8h.(2n)2 + (2n)3 = 512h3 + 384h2n
+ 96hn2 + 8n3
4- (4x + 9y)3
= (4x)3 + 3.(4x)2.9y + 3.4x.(9y)2 + (9y)3
= 64x3 + 432x2y + 972xy2 + 729y3
5- (14j + 11q)3
= (14j)3 + 3.(14j)2.11q + 3.14j.(11q)2 + (11q)3
= 2744j3 + 6468j2q + 5082jq2 + 1331q3